Assessing the impact of degraded urban green infrastructure on disaster risk resilience: A case study of Amman city centre, Jordan - Alshafei, Islam; Al-Kfouf, Safa’; Righelato, Pinar Ulucay (Politechnika Lubelska, 2025)
Amman, the capital of Jordan, has been growing rapidly, particularly in its city centre. This has led to the spread of high-density buildings and a loss of green spaces. As a result, the city's ecosystem services have been significantly reduced, making it more vulnerable to climate-related disasters such as floods and heatwaves. This study examines the current state of green space and green infrastructure (GI) in downtown Amman, using historical and recent maps from 1918 to 2020 to understand how urban development has affected the environment. The findings show that the amount of green space per person is far below the World Health Organization's recommended level, highlighting the decline of natural areas and the lack of green infrastructure in urban planning. The study emphasises the importance of green infrastructure in enhancing cities’ resilience to climate risks, while also noting that Amman has not done enough to implement it. This research provides valuable insights into how urban growth impacts green space and resilience in cities of the Global South, urging policymakers to prioritise green infrastructure to better manage disaster risks and promote sustainable urban development. © 2025 Budownictwo i Architektura.
Keywords: amman city centre; climate change; environmental degradation; Green Infrastructure (GI); Green Space (GS); urban resilience; urban sprawl